2020
DOI: 10.1177/0961203320967102
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity among incident Finnish systemic lupus erythematosus patients during 2000–2017

Abstract: The objective of the study was to examine the risk of other morbidities among patients with systemic lupus erythematosus (SLE). A total of 1006 adult new-onset SLE patients were identified during 1.1.2000- 31.12.2014 from the register of Social Insurance Institution. For each case three general population controls matched according to age, sex and place of residence at the index day were sampled from the population register. Both groups were followed up from the index date until the end of 2017 or until death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…For each patient, one to three population controls matched according to age, sex, and place of residence at the ID were randomly selected from the Population Register Centre. The detailed identification method is explained in more detail in a previous study [ 19 ]. Any clinical data, or data regarding whether the patients fulfilled the classification criteria for SLE were not available.…”
Section: Methodsmentioning
confidence: 99%
“…For each patient, one to three population controls matched according to age, sex, and place of residence at the ID were randomly selected from the Population Register Centre. The detailed identification method is explained in more detail in a previous study [ 19 ]. Any clinical data, or data regarding whether the patients fulfilled the classification criteria for SLE were not available.…”
Section: Methodsmentioning
confidence: 99%
“…1 Systemic lupus erythematosus is also related to a great number of comorbidities, such as cardiovascular diseases, infections and mood disorders. 2,3 Moreover, people with rheumatic diseases have a slightly higher risk for overall malignancy, and SLE is not an exception. 2,[4][5][6][7][8][9] Previous studies have shown that especially lymphomas and lung cancer are overrepresented among SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, North America has the highest estimates of SLE incidence and prevalence (23.2/100,000 person/year and 241/100,000 people, respectively [3]. The patients with SLE have a significant burden as a result of the disease's multi-organ involvement and the therapeutic options available [4]. All-cause standard mortality rates in SLE patients increased 2.6 times [3].…”
Section: Introductionmentioning
confidence: 99%